Studies on pseudomonas aeruginosa in drinking water from water suppliers consumed in Basra. - Al-Maliki, Ghazi M.; Haneff, Rajaa Abdul-Kadem (Al-Qadisiyah Journal of Pure Science, 2017)
Forty samples of drinking water collected from water supplierÂ´s consumed in different (10) regions in Basra city through six months at 2012 , have been analyzed bacteriologically. Pseudomonads members were selectively investigated and identified biochemically and showed as (14 %) . The majority of Pseudomonas spp. were found to be resistant to nalidixic acid, tetracyclin, ampicillin, and ceftazidim . The most effective antibiotics against Pseudomonas spp. were ciprofloxacin, gentamicin, colistin, and ceftriaxone. The high load of opportunists pathogen such as Pseudomonads in this study represents hygienic and quality challenge for consumed water , multiple antibiotic resistance detected among these bacteria might pose health significances, at least to some defined sensitive individuals, and should be considered properly.